Sunflower response to Boron supply when grown in a silty clay soil - Dhassi Khalid; Drissi Saad; Makroum Kacem; Nasreddine Fatima Ezzahra; Amlal Fouad; Aït Houssa Abdelhadi (Journal of the Saudi Society of Agricultural Sciences, 2020)
The objective of this study is to identify the requirements and the response of sunflower to boron (B) supply when grown in a silty caly soil. Two native soils B contents have been prospected. The soil “1” contains 0.66 mg kg−1 of B and soil “2” contains 0.19 mg kg−1 of B (Hot water extraction). For soil “1”, six levels of B supply (0, 2, 5, 10, 15 and 20 mg kg−1) were tested during 2015 season. For soil “2”, six B rates (0, 0.2, 0.5, 1, 5 and 10 mg kg−1) were tested during 2016 season. B was applied in the sodium form (Na2B8O13·4H2O). The experiments were conducted in containers. The results showed the absence of B symptoms deficiency on sunflower grown in the both studied soils. The kernels B content at harvest was around 20 mg kg−1 for all B rates. The kernels yield components (Kernels dry weight, 1000 kernels weight and number of kernels per head) and the contents of kernels on oil and on protein did not show any enhancement with B application. However, B supply higher than or equal to 5 mg kg−1 and 10 mg kg−1 in soil “1” and in soil “2”, respectively, induced phytotoxicity symptoms without affecting growth, biomass and oil production. Keywords: Boron, Sunflower, Silty clay soil, Phytotoxicity, Deficiency